Rolling foil fundamentals, pack lubrication, and areal density measurements - Huizar Jacob; Botha Willem; Esker Nicholas; Zach Mike (EPJ Web of Conferences)
Cold rolling is a fundamental technique for the nuclear target maker. In this talk, we will overview our eﬀorts at San José State University (SJSU) to inexpensively build out our cold rolling capabilities using a commercially available jewelers mill. In particular, we investigate the performance of diﬀerent pack lubricants on the rolling of metal such as titanium. We will also overview our approach to areal density measurements. These eﬀorts stem from a student-led project and align with core mission of the SJSU targetry group: that targetry is an important avenue to introduce the next generation to modern nuclear science.